2017
DOI: 10.1080/09712119.2017.1302877
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory responses related to coat traits of Brazilian native ewes: an adaptive approach

Abstract: Semi-arid conditions can adversely affect livestock productivity and change certain physiological parameters. The relationship between hair coat and thyroxine levels in Morada Nova ewes was evaluated through environmental factors, such as air temperature, relative air humidity, radiant and Black Globe Humidity Index to gain a better understanding of thermoregulation mechanisms in these animals. Measurements were taken from July to January in 383 Morada Nova ewes. The variables studied included rectal temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
5
17
1
1
Order By: Relevance
“…These results show the relatively high adaptability of the sheep to the climatic conditions of the Brazilian semiarid region and are similar to the findings of Rajab et al (1992), Sleiman and Abi Saab (1995), Quesada et al (2001), Al-Haidary (2004), McManus et al (2009), Castanheira et al (2010 and Leite et al (2017).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…These results show the relatively high adaptability of the sheep to the climatic conditions of the Brazilian semiarid region and are similar to the findings of Rajab et al (1992), Sleiman and Abi Saab (1995), Quesada et al (2001), Al-Haidary (2004), McManus et al (2009), Castanheira et al (2010 and Leite et al (2017).…”
Section: Resultssupporting
confidence: 78%
“…The H DE values observed in this study were lower than those found by Leite et al (2017) The low C T favored thermolysis. The presence of a thin layer of hair is beneficial for thermolysis because it tends to prevent the movement of hot air.…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations